Interferência e estudo fitossociológico da comunidade infestante na cultura da beterraba transplantada - de Carvalho, Leonardo Bianco [UNESP]; Pitelli, Robinson Antonio; Cecilio Filho, Arthur Bernardes; Bianco, Silvano; Guzzo, Caio Doria (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The objective of this research was to Study the phytosociological and critical interference periods of weed communities Oil transplanted beets. The treatments consisted of increasing weekly weedy/weed-free periods, starting it the second week after seedling transplanting. The weed community was evaluated based oil the number of individuals and their corresponding accumulated dry mass, for each weed population and evaluated period. The beets were harvested 91 days after transplanting, followed by evaluation of the cross-sectional diameter and marketable yield. The weed communities were composed mainly of Amaranthus viridis, Coronopus didymus, Galinsoga parviflora, Nicandra physaloides and Solanum americanum, and the populations were very similar. The period before weed interference and the total period of weed interference prevention were 51 and 35 days after transplanting, respectively. The beet yield in the weed-free treatment was 44.92 t ha(-1) and the reduction from weed interference was more than 70%.
Interference and phytosociological study of weed communities on transplanted beets
Keywords: Beta vulgaris L.; critical interference periods; Weeds